Visual impact of infill percentages for 3D printed radiologic simulators (Brazilian Journal of Radiation Sciences (BJRS), 2020)
The function of a simulator is to attenuate the radiation mimicking the different tissues of the human body. This study seeks to verify specifically one of the printing parameters, filling, in the final homogeneity of printed samples as the infill affects costs, print time and resultant attenuation to radiation. Sixteen cubes with 8 cm³ of each type of filament were printed in PLA with 27.5 ± 2.5% copper (Cu) and ABS with  infill variation from 15% to 90% in steps of 5%. The cubes were irradiated in a Phillips Brilliance CT 6 with 120kV, 200mA in 0.4mm slices and reconstructed with Standard filter. Each cube had the mean values of Hounsfield Units (HU) and standard deviation (SD) determined in a Region of Interest (ROI). Visually, the inner reticulate of each cube was evaluated by counting line pairs per millimeter (lp/ mm) through the DICOM Weasis viewer. It was observed that the HU values presents a linear behavior in terms of the infill variation. ROI values and line per millimeter are presented. Infill values above 50% for PLA + Cu and 40% for ABS showed a high homogeneity that do not allow differentiation in the line pairs.Values above those percentages are recommended to use in radiological simulators construction. It is suggested to perform this study for each filament, as one more parameter to be taken into account in the construction of radiologic simulators.